Super Encryption Cryptography for Land Certificate Data Security: A Case Study of the Jayapura City Land Agency - Ray Setiawan Panyuwa; Suharyadi Universitas Kristen Satya Wacana (International Journal Software Engineering and Computer Science (IJSECS), 2025)
This study introduces a lightweight, reproducible super-encryption framework designed to protect land certificate owner data at the Jayapura City Land Office. The system combines two classical algorithms—Rail Fence Cipher for transposition and Vigenère Cipher for substitution—through a structured, layered encryption pipeline implemented in Python. Testing was conducted on 50 simulated certificate owner names (10–15 characters each) under controlled conditions (Intel i5, 8 GB RAM, Windows 10). Black-box validation demonstrated 100% decryption accuracy with sub-10 ms total processing time per record. Robustness assessments revealed an average Shannon entropy increase of 41.6% and an avalanche rate of 47.8%, indicating enhanced ciphertext randomness. Results confirm that strategically layering classical ciphers delivers reliable confidentiality and integrity for small-scale, non-transactional datasets characteristic of land administration offices operating under resource constraints. The research offers a transparent, replicable model for securing identity fields and demonstrates the practical viability of super-encryption as a computationally efficient cryptographic solution for local government digital systems